The relationships between internal control, enterprise risk management, and firm performance in China / Zou Xiang - Zou, Xiang (2017)
The continuing economic uncertainties and unfortunate operational-risk events affecting firms around the world, a serious concern for both academics and industry commentators, have led to the development of risk management for organizations. In this context, the Internal Control Integrated Framework and the Enterprise Risk Management (ERM) Integrated Framework, which was proposed and developed by the Committee of Sponsoring Organizations of the Tread way Commission (COSO), have become the criterion reference of risk management programs for all entities. However, the valuation implications of internal control and ERM are mostly limited to financial institutions in European and American countries. Investigations of internal control or ERM are substantial but the relationship between them has not been rigorously studied yet. Moreover, there is also a shortage of empirical studies which compare the effects of internal control and ERM on firm performance. In that regard, this research is specifically designed for the purpose of addressing the shortcomings. This purpose is accomplished by exploring the association between internal control and ERM based on the relative impacts on firm performance for publicly listed firms located in China. Further to that, this research also attempts to understand if firm-specific characteristics can moderate the relationships between internal control, ERM, and firm performance in China. This research primarily uses quantitative data for the investigation. As has been anticipated, large firms were more likely to embrace internal control and ERM into their organizations, thus the sample selected for participation was sourced from firms listed in the CSI 300 Index. According to the time schedule of landmark events relative to internal control and ERM in China, this research also limited the sources of data collected to the 2008－2014 period. Collection of data streams depended mainly on the Bloomberg Database and Wind Financial Terminal (WFT). Content analysis was designed for the purpose of mining the supplementary data which were extracted from public information listed in firms’ financial statements and other media. To further evaluate the relationships between internal control, ERM, and firm performance, this research also adopted the Partial Least Squares Structural Equation Modeling (PLS-SEM) which included both the reflective and formative hierarchical construct models. Additionally, the Univariate Difference Test (UDT) was also used for comparing the differences of firm performance across internal control adoption, traditional risk management adoption, and ERM adoption so as to obtain a better understanding of the functions of risk management programs in firms listed in China. Results gained from the PLS-SEM indicated that there was a positive relationship between internal control adoption and firm performance in China; further, that relationship was moderated by firm size, leverage, asset opacity, and financial slack. Results also revealed that ERM adoption was negatively associated with firm performance; further, that association was moderated by leverage and dividend yield. Results also showed that internal control adoption had a positive effect on ERM adoption for publicly listed firms in China. The moderating relationship of firm size, leverage, beta, international diversification, industrial diversification, and the squared v value of insider ownership on internal control and ERM adoptions were noted to be significant. Results gained from the UDT illustrated a slightly different scenario where the adoption of internal control, traditional risk management, and ERM was noted to be all negatively related to firm performance in publicly listed firms in China. This finding suggested that internal control may mitigate risk for firms which have already established a sound framework for risk management.However, the effect of internal control on risk management was noted to be insufficient while the improvement in firm performance was also seen to be limited. Due to the inverse relationship seen between ERM adoption and firm performance, it was deduced that embracing ERM cannot add value to firms listed in China. The test results gained from applying the COSO components in this research suggested that firms in China need to increase the effectiveness of ERM by optimizing their strategy decisions. Since internal control was significantly associated with ERM, it is deduced that ERM was the mediator that can act on the association between internal control and firm performance. These results are useful as they provide key insights to scholars and practitioners on how to establish efficient internal control and ERM frameworks as well as on howto enhance firm performance by applying effective enterprise risk management systems.